Algebras of analytic functions on Banach spaces - A. V. Zagorodnyuk (Karpatsʹkì Matematičnì Publìkacìï, 2012)
The paper contains a survey of the most important results about structures of spectra of algebras of analytic functions of bounded type on Banach spaces and some new results in this area. Also, we have some applications to interpolations in algebras of analytic functions on unit balls of Banach spaces.